HMGA2 and Bach‐1 cooperate to promote breast cancer cell malignancy. Issue 10 (1st March 2019) - Mansoori, Behzad; Mohammadi, Ali; Asadzadeh, Zahra; Shirjang, Solmaz; Minouei, Mahsa; Abedi Gaballu, Fereydoon; Shajari, Neda; Kazemi, Tohid; Gjerstorff, Morten F.; Duijf, Pascal H.G.; Baradaran, Behzad
Abstract: During breast cancer progression, tumor cells acquire multiple malignant features. The transcription factors and cell cycle regulators high mobility group A2 (HMGA2) and BTB and CNC homology 1 (Bach‐1) are overexpressed in several cancers, but the mechanistic understanding of how HMGA2 and Bach‐1 promote cancer development has been limited. We found that HMGA2 and Bach‐1 are overexpressed in breast cancer tissues and their expression correlates positively in tumors but not in normal tissues. Individual HMGA2 or Bach‐1 knockdown downregulates expression of both proteins, suggesting a mutual stabilizing effect between the two proteins. Importantly, combined HMGA2 and Bach‐1 knockdown additively decrease cell proliferation, migration, epithelial‐to‐mesenchymal transition, and colony formation, while promoting apoptotic cell death via upregulation of caspase‐3 and caspase‐9. First the first time, we show that HMGA2 and Bach‐1 overexpression in tumors correlate positively and that the proteins cooperatively suppress a broad range of malignant cellular properties, such as proliferation, migration, clonogenicity, and evasion of apoptotic cell death. Thus, our observations suggest that combined targeting of HMGA2 and Bach1 may be an effective therapeutic strategy to treat breast cancer. Abstract : this study shows that the expression of high mobility group A2 (HMGA2) and BTB and CNC homology 1 (Bach‐1) is elevated and positively correlates in breast cancer. In addition, HMGA2 and Bach‐1 individual knockdown, but even more so combined knockdown suppress cell proliferation, migration, epithelial‐to‐mesenchymal transition, stemness, and clonogenicity and induces apoptosis. Thus, our study provides a rationale for combined targeting of HMGA2 and Bach‐1 in a cancer therapeutic setting.